Study of Binaural Auditory Cortical Response in Children with History of Recurrent Otitis - Oliveira, Leticia Sampaio; Oliveira, Anna Caroline Silva de [UNESP]; Alcantara, Yara Bagali [UNESP]; Vieira, Carolina Almeida [UNESP]; Ferreira, Dayse Mayara de Oliveira; Chagas, Eduardo Federighi Baisi; Frizzo, Ana Claudia Figueiredo [UNESP] (Georg Thieme Verlag Kg, 2020)
Introduction Any type of sensory deprivation in childhood resulting from conductive hearing loss may impair the development of peripheral and central auditory pathway structures with negative consequences for binaural processing. Objective To characterize and compare monoaural and binaural auditory responses in neonates and children without and with a history of recurrent otitis. Methods The study included participants from 0 to 8 years and 11 months old, in good general health conditions, of both genders, divided into a control group, with no history of otitis, and a study group, with history of recurrent otitis. Cortical potential with speech stimulus /ba/-/da/ was used as collection procedure. The arithmetic calculation of the 512 points of the wave was performed to obtain the grand average of the waves of the subjects in both groups. The Shapiro-Wilk and mixed repeated measures analysis of covariance (ANCOVA) statistical tests were performed to analyze the group effect, the condition, and the interaction (group versus condition) controlling the effect of the age-sex covariable. Results There was a statistically significant difference between the groups for all latency values; and for the P1, N1, P2, and N2 latencies, the differences between the groups occurred in the three analyzed conditions (right and left ears and binaural), revealing the influence of sensory deprivation. There were no significant differences in relation to wave amplitudes. Conclusion There are differences in the cortical potential with speech stimuli and in the binaural interaction component of children with and without history of recurrent otitis.
Keywords: auditory evoked potentials; electrophysiology; child; otitis; hearing